Regeneração de rejeito espuma de SBR através de extrusão no estado sólido e incorporação em SBR virgem - Tozzi, Kaique Afonso (Universidade Federal de São Carlos, 2017)
The objective of the present work is the study of the recycling of vulcanized rubber foam waste from the footwear industry through the solid state extrusion process known as Solid State Shear Extrusion (SSSE). The industrial waste, previously ground in the industry responsible for its supply, was characterized in terms of particle size, density and amount of mineral fillers and then regenerated by SSSE. The influence of the process temperature on the material reclaiming was investigated using different temperature profiles in the extruder. The presence of a possible devulcanization agent during extrusion was also studied, in this case with the presence of benzoyl peroxide. After subjecting material to the SSSE process under various conditions of temperature and peroxide quantity, the waste was characterized in terms of soluble content by Sohxlet Extraction in Toluol, and its granulometry classified by sieving. The next stage of the work consisted in the study of the re-incorporation of the regenerated material under the different process conditions in the random copolymer styrene-butadiene rubber, SBR, in the amount of 40 phr of reclaimed rubber, along with vulcanization reagents for later vulcanization. By way of comparison, composition with the original waste rubber (without reclaiming) was also prepared. The compositions were molded and revulcanized by compression molding at a temperature determined by Differential Exploratory Calorimetry and oscillatory disk rheometry. From the molded plates, specimens were obtained by stamping and subjected to mechanical tensile tests and crosslinks density. Comparing the results, especially the mechanical properties, of the regenerated and non-regenerated waste compositions, the advantages of the use of regeneration of the rubber residues by SSSE were evident. From the results, it was also possible to hypothesize about the mechanisms of regeneration and devulcanization involved in the process, which may be useful in the implementation of the reuse process.
Regeneration of industrial foam waste of sbr through solid state shear extrusion and incorporation of its on raw SBR
Keywords: Regeneração de elastômero; Extrusão no estado sólido; Desvulcanização; Reciclagem de rejeito industrial; Elastomer reclaiming; Solid state shear extrusion; Devulcanization; Industrial waste recycling; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS